PENGEMBANGAN MEDIA POSTER BERBASIS PENDIDIKAN KARAKTER UNTUK MATERI GLOBAL WARMING - SRI MAIYENA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
This research was done because of the students’ difficulties in understanding the concept of global warming and implementing character values so that it needed to design poster media based character education. This research was aimed to see the effectiveness of poster media based character education that was already developed in Ilmu Alamiah Dasar subject. The design of the research was a research development. The effectiveness of poster media was gotten from testing to the students who had conducted Ilmu Alamiah Dasar subject. The instrument of the research was questionnaire. The result of the rsearch showed that developing poster media based character education was very effective according to the students with percentage 81.9%. Kata kunci: media poster berbasis pendidikan karakter, praktis, global warming